Amplitude analysis of the D s + $$ D_s^{+} $$ → π − π + π + decay - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; B. Adeva; M. Adinolfi; P. Adlarson; H. Afsharnia; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics, 2023)
Abstract A Dalitz plot analysis of the D s + $$ D_s^{+} $$ → π − π + π + decay is presented. The analysis is based on proton-proton collision data recorded by the LHCb experiment at a centre-of-mass energy of 8 TeV and corresponding to an integrated luminosity of 1.5 fb −1. The resonant structure of the decay is obtained using a quasi-model-independent partial-wave analysis, in which the π + π − S-wave amplitude is parameterised as a generic complex function determined by a fit to the data. The S-wave component is found to be dominant, followed by the contribution from spin-2 resonances and a small contribution from spin-1 resonances. The latter includes the first observation of the D s + $$ D_s^{+} $$ → ω(782)π + channel in the D s + $$ D_s^{+} $$ → π − π + π + decay. The resonant structures of the D s + $$ D_s^{+} $$ → π − π + π + and D + → π − π + π + decays are compared, providing information about the mechanisms for the hadron formation in these decays.